Distribution of Seafarers’ Earnings Versus Salary Distribution in Poland – Statistical Analysis - Anna Turczak (Studia Maritima)
Although remuneration is not the sole determinant of workplace attractiveness, it is considered the most crucial factor. The aim of this article is to assess the pattern of seafarers’ incomes in comparison to salaries in the national economy. To achieve this goal, a statistical analysis of earnings distribution in the seafarers’ cohort and the distribution of all earnings in Poland was conducted, followed by relevant comparisons. The article begins with an introduction presenting the research problem and concludes with key findings. The main part of the work consists of a detailed description of the applied methodology and the presentation of the obtained results along with their interpretation. All calculations were based on data from the Central Statistical Office. The validity of the hypothesis was confirmed, indicating that the income distribution in the seafarers’ cohort has a higher average value but smaller dispersion, skewness, and concentration than the income distribution in the entire population of employees in Poland.